PENGARUH CSR DISCLOSURE TERHADAP FIRM’S TOTAL RISK DENGAN TAX PAYMENT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TERINDEKS LQ45 PERIODE 2021-2023 - Immanuel Ari Nurpratama; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2026)
This study aims to investigate and provide empirical evidence regarding the impact of Corporate Social Responsibility (CSR) Disclosure on firm total risk in LQ45-indexed companies. It further examines the moderating role of tax payment on the relationship between CSR disclosure and firm's total risk. The sample comprises LQ45-indexed companies for the 2021–2023 period. The independent variable is CSR Disclosure, while the dependent variable is firm total risk. This study also incorporates several control variables, namely market-to-book value (MVB), ROA, and Firm Size. Utilizing a quantitative approach, the analysis is performed using panel data regression analysis.The results indicate that CSR disclosure has a significant negative effect on firm's total risk. Conversely, the tax payment variable is unable to moderate the relationship between CSR disclosure and firm's total risk. These findings suggest that CSR disclosure can foster harmonious relationships and increase mutual trust between management and all stakeholders, while also serving as a positive signal for investors. Furthermore, paying taxes in compliance with regulations is a standard obligation for every corporation to maintain its legality. The market does not grant a "bonus" in the form of additional risk reduction simply because a company fulfills its basic obligations.